2012
DOI: 10.1002/ange.201201012
|View full text |Cite
|
Sign up to set email alerts
|

Die Trifluormethylierung von Arenen und Heteroarenen

Abstract: Vielversprechendes: Der immer größer werdende Bedarf an trifluormethylierten Arenen und Heteroarenen stellt eine große Herausforderung dar, der mit der Entwicklung von Trifluormethylierungsreaktionen begegnet wurde. In diesem Highlight werden mehrere effektive Ansätze für die Trifluormethylierung im späten Reaktionsstadium und die Verwendung von einfachen und preiswerten Trifluormethylierungsreagentien vorgestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[1] As with all fluorine-containing derivatives, the incorporation of the trifluoromethyl motif, which is absent in Nature, [2] into an organic molecule results in deep modifications of its chemical and physical properties including, among others, its basicity, hydrophobicity, conformation, binding selectivity or metabolic stability. [4] Besides the development of these new trifluoromethylation processes, new trifluoromethylated building blocks are also emerging. [4] Besides the development of these new trifluoromethylation processes, new trifluoromethylated building blocks are also emerging.…”
Section: Introductionmentioning
confidence: 99%
“…[1] As with all fluorine-containing derivatives, the incorporation of the trifluoromethyl motif, which is absent in Nature, [2] into an organic molecule results in deep modifications of its chemical and physical properties including, among others, its basicity, hydrophobicity, conformation, binding selectivity or metabolic stability. [4] Besides the development of these new trifluoromethylation processes, new trifluoromethylated building blocks are also emerging. [4] Besides the development of these new trifluoromethylation processes, new trifluoromethylated building blocks are also emerging.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Trifluoromethylation of aromatic compounds is a hot research area and effective methods have been established. [7] In contrast, it is apparent that trifluoromethylation of simple alkenes is still developing. [8][9][10][11] Recently, Parsons and Buchwald,…”
mentioning
confidence: 95%
“…These results indicated that the strong electron-withdrawing di-and trifluoromethyl groups are critical for the reactivity and selectivity of this decarboxylative Mannich reaction. [10] The utility of this decarboxylative Mannich products was demonstrated by the following transformations (Scheme 2). Starting from the adduct (R)-3 i, a simple reduction of the ester moiety with NaBH 4 , followed by cyclization to the amide nitrogen, gave 5,9b- (5) containing an azetidine moiety, which is a key subunit found in a number of bioactive natural products (Scheme 2 a).…”
mentioning
confidence: 99%